PENGARUH SELEKSI DAN PELATIHAN TERHADAP KINERJA KARYAWAN ROCKET CHICKEN DI GRESIK - Mubbaroq, Abdullah (Fakultas Ekonomi Universitas Gresik, 2019)
Rocket Chicken in Gresik. This research is important to learn about positive changes that occur in employee performance at Rocket Chicken store. This research uses quantitative with multiple linear analysis. The number of samples taken as many as 52 respondents and collected data was done by questionnaire to collect data. The results of this study are the accountability of Rocket Chicken employee performance in Gresik has a significant positive effect on improving employee performance.DOI 10.5281/zenodo.3629919